The operation of the lupon tagapamayapa in selected barangays of Jaro, Iloilo City - Betita, Jomar Alyzar A.
This research anlyzes the efficiency of the operation of the Lupon Tagapamayapa in selected barangays of Jaro City. Its objectives cover analysis of aspects of the operation of the lupon within teh area such as the adequacy of knowledgethat the members of the lupon to the functions set by the Katarungang Pambarangay Law, the settlement cases handled by the lupon within the area and the results of these disputes and the problems encountered by the lupon in its operation., This study showed that majority of the Lupon members have inadequate knowledge regarding the operation of the Lupon and lacks the necessary knowhow in the implementation of amicable settlement in the area, Majority of the lupon in the area failed to meet the second function set by the law which is to conduct monthly meetings. The research also pointed out the deviations committed by the lupon in enforcing amicable settlement. The problems of the lupon deal mostly with the lack of financial support extended to them by the government.